The Influence of Teacher's Teaching Skills on Students' Learning Interest in Fiqih Courses at MAN 2 Sukabumi - Mumin, U Abdullah; Khutomi, Budi Munawar; Herri Azhari, Herri; Faqih, Usman; Acip, Acip (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Teachers as professionals must have teacher competence, where these competencies are visually implemented in the teacher's ability to provide teaching skills during the learning process. One way that the teacher can do, the teacher's teaching skills are essential in learning so that they can foster student learning enthusiasm and facilitate the achievement of learning objectives. This study aimed to analyze teacher skills' effect on students' learning interest in Fiqih subjects. The research was conducted at MAN 2 Sukabumi in February-April 2019. This type of research is quantitative descriptive with Proportionate Stratified Random Sampling. Data collection techniques by observation, interviews, and Guttman scale questionnaires on the variables of teacher teaching skills and students' learning interests used validity, reliability, and normality tests. The data analysis technique uses linear regression analysis. The results of the study showed that the teaching skills of teachers at MAN 2 Sukabumi for the 2018/2019 school year were "High" with an average score of 13.89, and the most significant contribution came from the teacher's skill indicator of opening and closing lessons of 76.1%. Furthermore, student learning interest in Fiqih subjects is also included in the "High" category with an average value of 11.47. The most significant contribution comes from the student's attention indicator of 63.7%. The teacher's teaching significantly affected learning interest in students' Fiqih subjects at MAN 2 Sukabumi for the 2018/2019 academic year by 62.9%, while other factors influenced the remaining 37.1%.